2022
DOI: 10.3390/horticulturae8110999
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Fruit Weight, Size and Organic Acid Content in a Distant Hybrid Population of Longan ‘Huanongzao’ and Lychee ‘Ziniangxi’

Abstract: The type and content of organic acids in fruits are important factors that determine the traits, such as the nutrition and flavor of fruits. Fruit weight and size are also very important economic characters in fruit breeding research. To investigate the inheritance patterns in longan, fruit organic acid contents, weight, and size were measured in the distant hybridization progenies of longan ‘Huanongzao’ and lychee ‘Ziniangxi’. The results revealed that the malic acid accumulation exhibited mid-parent heterosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Fruit size and weight are very important economic traits in fruit breeding research [30]. In this study, our results have found significantly smaller weight and size of MT fruits, but significantly larger MT/Pt fruits (Table 1).…”
Section: Natural Variation and Rootstocks Effect The General Morpholo...supporting
confidence: 60%
“…Fruit size and weight are very important economic traits in fruit breeding research [30]. In this study, our results have found significantly smaller weight and size of MT fruits, but significantly larger MT/Pt fruits (Table 1).…”
Section: Natural Variation and Rootstocks Effect The General Morpholo...supporting
confidence: 60%
“…Citric acid was also predominantly found in various cultivars of rambutan [ 36 ], while tartaric acid and malic acid were mainly found in different cultivars of lychee [ 37 ]. Similarly, malic acid was also predominantly detected in longan [ 38 ]. Compared to other fruits in the same family, N. hypoleucum Kurz expressed higher amounts of citric acid [ 36 , 37 , 38 ], causing a sour taste.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, malic acid was also predominantly detected in longan [ 38 ]. Compared to other fruits in the same family, N. hypoleucum Kurz expressed higher amounts of citric acid [ 36 , 37 , 38 ], causing a sour taste.…”
Section: Discussionmentioning
confidence: 99%
“…Coordinated efforts to breed for lower oxalate levels in other crop species, such as spinach (Shi et al 2016), rhubarb (Libert 1987), tomato (Chakraborty et al 2013), winter wheat (Matros et al 2017), and soybean (Francis et al 2020), are in progress. Regarding rhubarb, a crop species in the same Order as beet, low (h 2 5 0.3-0.38) narrow-sense heritabilities have been estimated for oxalic acid concentration, whereas estimates of broad-sense heritability are moderate (H 2 5 0.58) for winter wheat (Matros et al 2017) and high (H 2 5 0.97) for populations resulting from a hybridization event between longan and lychee (Wang et al 2022). Research of other crop species has suggested that the type and quantity of exogenous nitrogen applied may influence the amount of oxalic acid found in plant tissues (Tian et al 2008;Rahman et al 2012;Liu et al 2015).…”
Section: Discussionmentioning
confidence: 99%